Biodiversitas Serangga Aerial dan Serangga Tanah Serta Korelasinya dengan Faktor Abiotik Pada Lahan Pertanian di Kabupaten Dompu - Khatimah, Ainul; Muharyati, Yully; Ardiansyah (Universitas PGRI Silampari, 2025)
Land conversion in Dompu Regency is increasingly rapid due to the high demand for corn. Many studies have shown that land conversion not only results in a decrease in the number of species but also changes the structure and composition of insect communities. The purpose of this study was to analyze the diversity, correlation of diversity with abiotic factors and distribution patterns of aerial and ground insects found in agricultural land. The study was conducted in four locations: corn fields, rice fields, sacha inchi fields, and intercropping fields. The research method used was a quantitative exploration method that combines active and passive observations including VES, Sweeping nets, Pitfall traps, and yellow traps. The results of insect identification at the four research locations found 8 orders with 34 species divided into 4.37% decomposers, 17.27% pollinators, 31.59% predators, and 46.77% pests. The highest diversity was found in corn fields with an index of 3.06, followed by rice fields with 3.04, sacha inchi fields with an index of 3.007, and the lowest in intercropping fields with an index value of 2.96. The results of the Pearson correlation analysis found that humidity has a positive influence on species diversity and evenness, but is negatively correlated with dominance.